Hubungan Kepatuhan Minum Obat Dengan Rerata Glukosa Darah Sewaktu di Poliklinik Penyakit Dalam - Prabu Ageng, Franciscus Asisi Gada; Subiyanto, Paulus; Pujiastuti, Theresia Tatik (I Care Jurnal Keperawatan STIKes Panti Rapih, 2024)
ABSTRACT Background:Type 2 diabetes mellitus is a disease with the typical characteristics of chronic hyperglycemia due to insulin resistance. Compliance with taking medication for type 2 DM patients can affect blood sugar. Objective:This study aims to determine the relationship between medication adherence in DM patients and average blood glucose over time Method :Researchers used a cross sectional method using accidental sampling technique in type 2 diabetes mellitus patients based on 72 populations according to the inclusion criteria, obtaining 52 respondents. Correlation analysis uses the Spearman test results:The results of the study showed that the highest type of treatment for type 2 DM patients was 42.3% with single and combination oral drugs. Compliance with taking medication showed a poor category of 44.2%. The average blood glucose of type 2 DM respondents was in the Low category, namely 46.2%. The results of the Spearman correlation test obtained a p value of 0.003 (p 0.05) and a correlation coefficient value of -0.406 Conclusion:There is a significant relationship between adherence to taking medication and the average blood glucose level of type 2 DM patients in the internal medicine clinic at Panti Rini Hospital, Yogyakarta. Patients with a low level of adherence to taking medication tend to have a high average blood glucose, but the higher the level of adherence to taking medication, the lower the patient's average blood glucose. Recommendations:Hospitals as health service centers are advised to increase education regarding having their own glucometer and having independent blood pressure monitoring records, education on 7 self-care behaviors for glycemic management of DM patients and a multidisciplinary approach. Keywords: Medication Compliance; Average Blood Glucose; Diabetes Mellitus Type 2